Hubungan Self-Esteem Dan Loneliness Pada Remaja Pengguna Media Sosial (Instagram) - Hanifah Salma Putri; Rida Yanna Primanita (Science and Education Journal (SICEDU), 2026)
This study aims to determine the relationship between self-esteem and loneliness among adolescents who use Instagram social media in Bukittinggi City. The study used a quantitative approach with purposive sampling techniques involving 165 adolescents aged 15–19 years. Data were collected using the Rosenberg Self-Esteem Scale (RSES) and the UCLA Loneliness Scale. The reliability test results showed a Cronbach's Alpha value of 0.849 for self-esteem and 0.859 for loneliness. Data analysis using the Spearman Rank Correlation test showed a correlation coefficient value of -0.400 with p < 0.001, which means that there is a negative and significant relationship between the two variables. The higher the self-esteem of adolescents, the lower the level of loneliness they feel. These findings indicate the important role of self-esteem in maintaining the psychological well-being of adolescents and the need for digital literacy to encourage healthy and balanced use of social media.